PERBEDAAN PENGARUH PENGGUNAAN METODE KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SENI RUPA DI KELAS VII SMP NEGERI 9 PADANG - LESTINA GUSTI, Drs. Wisdiarman, M.Pd, Drs. Mediagus (Serupa The Journal of Art Education, 2014)
The purpose of this research was to determine the effect of jigsaw cooperative learning model toward students’learning outcomes in SMPN 9 Padang.The effect can be seen from the differences in students’learning outcomes of students who were taught by using the jigsaw cooperative learning model than the learning outcomes of students who were taught by using conventional learning models in learning art.The hypothesis of study is”there is a significant difference between the learning outcomes than the students who were taught by using conventional methods in the art subjects at SMP N 9 Padang.Type of research is experimental research. The population in the research were all students of class VII in SMPN 9 padang which amount around 199 people.The results of this research from the processing of the data showed the significant differences between the learning outcomes than students who were taught by the jigsaw method of cooperative learning outcomes than students who were taught by using conventional methods in the art subjects in class VII smpn 9 Padang.Key word : Jigsaw cooperative learning model,learning outcomes